Development of Defect Tracking System - Syed Masohor, Syed Muhamad Akif; Abdul Hamid, Norhamreeza (Applied Information Technology And Computer Science, 2023)
Defect Tracking System is a tool to keep track of a list of bugs that have been reported during the testing or development phase of a system. The current process of developers and testers from the chosen case studies does not use any kind of specific tools to keep track of the list of bugs discovered during or after system development. Currently, the spreadsheet has been used to list defect that has been found and use cloud storage to synchronize with other users. The main purpose of this system is to improve the efficiency of testers and developers to keep track of bugs found during the development process. There are six modules which are the registration and login module, bug submission and display module, communication module, notification module, and report generation module. This system will help developers and testers to report, track and discuss everything regarding the project development more efficiently.